2020
DOI: 10.3390/biology9030056
|View full text |Cite
|
Sign up to set email alerts
|

Putative Protein Biomarkers of Escherichia coli Antibiotic Multiresistance Identified by MALDI Mass Spectrometry

Abstract: The commensal bacteria Escherichia coli causes several intestinal and extra-intestinal diseases, since it has virulence factors that interfere in important cellular processes. These bacteria also have a great capacity to spread the resistance genes, sometimes to phylogenetically distant bacteria, which poses an additional threat to public health worldwide. Here, we aimed to use the analytical potential of MALDI-TOF mass spectrometry (MS) to characterize E. coli isolates and identify proteins associated closely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…The majority of these studies used pathogens such as Staphylococcus aureus and the βlactam antibiotic family (Sogawa et al, 2017;Wang et al, 2018;Tang et al, 2019). Therefore, there are very few published data concerning other relevant clinical or foodborne pathogens or antimicrobials such as the quinolones (e.g., ciprofloxacin) and macrolides (e.g., erythromycin and azithromycin) (Sabença et al, 2020;Sousa et al, 2020). However, macrolides and quinolones are frontline antibiotics used to treat severe infectious gastroenteritis and categorized by the World Health Organization (WHO) as critically important in human medicine (WHO, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies used pathogens such as Staphylococcus aureus and the βlactam antibiotic family (Sogawa et al, 2017;Wang et al, 2018;Tang et al, 2019). Therefore, there are very few published data concerning other relevant clinical or foodborne pathogens or antimicrobials such as the quinolones (e.g., ciprofloxacin) and macrolides (e.g., erythromycin and azithromycin) (Sabença et al, 2020;Sousa et al, 2020). However, macrolides and quinolones are frontline antibiotics used to treat severe infectious gastroenteritis and categorized by the World Health Organization (WHO) as critically important in human medicine (WHO, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additional examples in the analytical step include the identification of bacterial and fungal species using matrix-assisted laser desorption/ ionization time of flight (MALDI-TOF) mass spectrometry. Machine learning based algorithms can link mass spectral profiles to specific clinical phenotypes such as antibiotic resistance [43,44]. e Surveillance of reagent lots performance with internal and external controls and automated reporting in connection to specific used lots of time [129] Imaging Are there bacteria on the microscope slide?…”
Section: Opportunities For Digitalization In the Microbiology Diagnostic Processmentioning
confidence: 99%
“…e Automated screening for pathogen similarities, e.g., resistance profile or automated bioinformatics [130,131] Post-analytics Highlight important data Is there a potential bacterial phenotype? e Detection of resistance by analysing MALDI-TOF spectra [43,44] Sepsis treatment What is the best treatment for the patient? e Prediction of sepsis, and best treatment, e.g., volume and antibiotics for the patient…”
Section: Opportunities For Digitalization In the Microbiology Diagnostic Processmentioning
confidence: 99%
“…The lengthy nature of conventional methods for bacterial identification and susceptibility testing purposes has resulted in the empirical use of broad-spectrum antibiotics and led to the spread of resistance [85]. Aiming at rapid and reliable detection of AMR, numerous studies have recently been reported on the use of ML algorithms in combination with the output of several analytical techniques, such as MALDI-TOF MS [89,96,[110][111][112][113][114][115][116][117][118], vibrational spectroscopy [102,103,119], whole-genome sequencing [120][121][122][123][124], a microscopy-based platform [125], and acousticenhanced flow cytometry [126].…”
Section: Detection Of Antimicrobial Resistancementioning
confidence: 99%
“…Using an RF model on MALDI-TOF MS spectra, Huang et al [115] were able to correctly identify 93% of carbapenem-resistant and all carbapenem-sensitive Klebsiella pneumoniae isolates. Moreover, successful systems using a combination of MALDI-TOF MS data and ML algorithms were recently reported for the detection of extended-spectrum betalactamase-producing Escherichia coli (E. coli) strains [117], rapid detection of cfiA metallo-b-lactamase-producing Bacteroides fragilis strains [118], and identification of fluconazole resistance in Candida albicans strains [96].…”
Section: Detection Of Antimicrobial Resistancementioning
confidence: 99%